A TGF-loading hydrogel scaffold capable of promoting chondrogenic differentiation for repairing rabbit nasal septum cartilage defect - Zhang, Dan; Su, Ying; Sun, Peng; Liu, Xingzhi; Zhang, Lin; Ling, Xuwei; Fan, Yuhui; Wu, Kang; Shi, Qin; Liu, Jisheng (Frontiers in Bioengineering and Biotechnology, 2022)
Hydrogel-based tissue engineering has been widely used to repair cartilage injury. However, whether this approach can be applied to treat nasal septum cartilage defects remains unclear. In this study, three gelatin methacrylate-based scaffolds loaded with transforming growth factor (TGF)-β1 (GelMA-T) were prepared, and their effects on repair of nasal septum cartilage defects were examined. In vitro, the GelMA-T scaffolds showed good biocompatibility and promoted the chondrogenic differentiation of bone mesenchymal stem cells. Among three scaffolds, the 10% GelMA-T scaffold promoted chondrogenic differentiation most effectively, which significantly improved the expression of chondrocyte-related genes, including Col II, Sox9, and ACAN. In vivo, 10% GelMA-T scaffolds and 10% GelMA-T scaffolds loaded with bone mesenchymal stem cells (BMSCs; 10% GelMA-T/BMSCs) were transplanted into a nasal septum cartilage defect site in a rabbit model. At 4, 12, and 24 weeks after surgery, the nasal septum cartilage defects exhibited more complete repair in rabbits treated with the 10% GelMA-T/BMSC scaffold as demonstrated by hematoxylin & eosin, safranine-O, and toluidine blue staining. We showed that GelMA-T/BMSCs can be applied in physiological and structural repair of defects in nasal septum cartilage, providing a potential strategy for repairing cartilage defects in the clinic.